SH2 Domain Binding: Diverse FLVRs of Partnership - Jaber Chehayeb, Rachel; Boggon, Titus J. (Frontiers in Endocrinology, 2020)
The Src homology 2 (SH2) domain has a special role as one of the cornerstone examples of a ‘modular’ domain. The interactions of this domain are very well conserved, and have long been described as a bidentate, or “two-pronged plug” interaction between the domain and a phosphotyrosine (pTyr) peptide. Recent work has, however, highlighted unusual features of the SH2 domain that illustrate a greater diversity than was previously appreciated. In this review we discuss some of the novel and unusual characteristics across the SH2 family, including unusual peptide binding pockets, multiple pTyr recognition sites, recognition sites for unphosphorylated peptides, and recently identified variability in the conserved FLVR motif.